Factors Affecting Gluten Production And Its Rheological Characterizations - Abang Zaidel, Dayang Norulfairuz (2007)

(untitled)
In this thesis, focus was given upon three factors affecting gluten production and development during dough mixing namely mixing time, salt levels and water levels. Gluten production was examined in terms of quantity and quality of gluten. Quantity of gluten was measured in terms of wet and dry gluten content. Wet gluten content was determined by weighing the gluten obtained from the dough washed under running tap water. The wet gluten was dried using air oven drying method to obtain dry gluten content. The quality of gluten was determined from the analysis of volume expansion, extensibility and rheological characterization. The volume expansion analysis was performed by frying the wet gluten in hot oil at 170 o C in deep fryer for 15 minutes. The volume of fried gluten was measured using mustard seed displacement method and the difference between the volume of fried gluten and the volume of wet gluten is measured as volume expansion of gluten.The main problem encountered in performing gluten and dough extensibility test is to hold the sample so that it does not break at the jaws that hold the sample. Thus it is one of the objectives in this study to build a simple set-up of tensile test to determine gluten extensibility, which is one of the most common measurements employed in determining the quality of gluten. A simple set-up of tensile test which is attached to Instron 5566 has been build to determine gluten extensibility. Gluten strip of about 10 mm x 10 mm x 70 mm was clamped at two ends using plastic clips and extended at the centre by hook at speed of 300 mm min -1 . Extensibility parameters such as original gluten length, gluten length at fracture, measured force, actual force acting on the gluten strips, strain and stress were obtained using the formulas derived from the results of tensile test. The tensile test set-up was successful in terms of providing the gluten extensibility measurements and also the gluten did not fracture at the clamping area. Rheological characteristics of gluten, K and n, were obtained by fitting stress-strain curve following an exponential equation, e s = Ken . Two types of flour, strong and weak, were used as a comparison. Correlation between two analyses measurements of the gluten quantity and quality are determined at the end of this thesis. An adequate polynomial equation model which fits the data was produced from Design Expert V.6.0.4. P-value, R 2 and lack-of-fit value were determined to verify the fitness of the polynomial model equation to the actual data and thus can be used as a good prediction of the data. The results from Design Expert were then transferred to Microsoft Excel file where the graph of the response was plotted against the three factors studied.Results suggested that from the three factors studied, salt gave the most significant effect (0.0001 < P < 0.02) on the gluten quantity and quality. As salt level increases, it decreases the wet and dry gluten content. The volume expansion of gluten and the extensibility seem to decrease with increasing salt level. This indicates that gluten network strength reduces and it does not mix into elastic dough as salt level increases. The next significant factor was water level (0.0001 < P < 0.67). Mixing time was the least significant factor among the three (0.0001 < P < 0.95). For all factors studied, the results for strong flour were higher than the weak flour in the quantity, volume expansion and also extensibility. This demonstrates that the quality of gluten is affected by the protein content of the flour. All correlations between two analyses of quantity and quality measurements show positive coefficient of correlation (R). Strong correlation between (i) gluten quantity and volume expansion (R > 0.75), (ii) gluten quantity and extensibility (R > 0.80) and (iii) volume expansion and extensibility of gluten (R > 0.60) were obtained for strong flour compared to weak flour (R > 0.45; R > 0.50; R > 0.30, respectively). These results indicate that the quality of gluten is influenced by the protein content of the flour and the extensibility and volume expansion of gluten is positively correlated. These correlations could be used in the food industry to improve the gluten quantity and quality in the future.